Integrating the Work-Life Interface During Expatriation: A Case Study of Expatriate Mining Professionals - Richardson, Julia; McKenna, Stephen; Dickie, Carolyn; Kelliher, C. (Springer International, 2015)
The global mining industry is characterized by increasing demands for international mobility. With growing calls for more work-life balance across many professions, therefore, it offers a potentially important context in which to explore the impact of international mobility on the interface between work and personal life. Drawing on a study of 60 expatriate mining professionals, this chapter reports widespread perceptions that during expatriation ‘work’ and ‘life’ become more integrated - particularly in situations where organizational support systems are limited. Specifically, it will report how interviewees relied on work colleagues for support and how that reliance created more integration between work and non-work domains. It will also report the perceived impact of financial status and job security on the work-life interface- a relatively unexplored theme in the current literatures. Drawing the findings of the chapter together, we will suggest that this increased integration encourages a reordering of the work-life interface during expatriation.